PELAKSANAAN TATA NIAGA KELAPA DI KABUPATEN INDRAGIRI HILIR TAHUN 2019 DALAM PERSPEKTIF EKONOMI POLITIK - ", Rosmawati; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Riau Province have a sufficiently expansive coconut plantation area, around 422.595 hectares,  approximately 83% of said area is contained within the Indragiri Hilir Regency. Indragiri Hilir regency government have made Local Regulation Number 3 Year 2018 (Peraturan Daerah Nomor 3 Tahun 2018) regarding the The Execution of Coconut Commerce to regulate the coconut chain of commerce in Indragiri Hilir regency, however an issue that have arisen is that the price of coconut amongst the farmers  as of 2019 is still very low. The question that this research will solve is how the coconut commerce in Indragiri Hilir regency is being executed and what are the factors that affect the execution of coconut commerce in Indragiri Hilir regency.            This research uses the qualitative approach with descriptive type approach. The type and research data sources are separated into primary data in the form of purposive informant gathering technique and secondary data in the form of supporting data regarding the execution of coconut commerce. The data are gathered using interview and documentation techniques.The results of the research regarding the execution of coconut commerce in Indragiri Hilir regency year 2019 within the political economy perspective, have not yet been able to be optimally implemented and enforced. This issue is caused by the execution of said local regulation from all involved department are still at the socialization stage. In the year 2019 and even until 2020 the coconut industry have not been able to give or decide a standard price margin towards coconut businessman/gatherer because the lack of partnership cooperation. The government’s plan to open a corporation that moves within the management of coconut  based produce and attempt to operate a special coconut port as of 2020 said plans are still in the managerial recruitment and business plan formulation phase and thus they are yet to operate and also the program to preserve and repair the farmers plantation  from The Plantation Department have been reduced,  some are not even executed. The factors that affect the execution of coconut commerce are the Regent’s regulation to further proceed the execution of the local regulation have not yet been made by related Departments. The Indragiri Hilir regency also have not yet possess a special market for coconut, in the year 2019 the program from the Department of Plantation to  preserve and repair the farmers plantation mostly remains as unexecuted programs and the unequal socialization towards corporations by The Deparment of Commerce and Industry. Keywords : Local Government, Execution of Coconut Commerce, Economic Politic